The Influence of Biochar and Substrates Application on the Parameters and Yield of Mini-Tubers of the Charoit Potato Variety - Rodionenko Alexander (EDP Sciences, 2021)
The objects of research were potato meristem plants of the Charoite variety, mass and the number of mini-tubers grown on the “Agrobalt S” peat fertilizer and in a mixture of “ORVI” and biochar substrate in a closed greenhouse. A statistically significant effect of the use of this substrate and biochar on the increase in the number of standard mini-tubers relative to the control variant using only peat soil was established. The yield of standard tubers (9 – 60 mm) was 78 % when using “Agrobalt S” peat soil; 10 % of the substrate "ORVI" and 5 % of biochar, 78 %; 20 % of the substrate “ORVI” and 5 % of biochar, 77 %. A decrease in the standard material of mini-tubers of the Charoite variety against the background of an increase in quantitative indicators does not occur when using the substrate and biochar. Evaluation of latent viral infection of meristem plants and mini-tubers grown from them was performed by ELISA (Sandwich variant) in July and February and did not reveal latent infection in any of the variants. The determination of growing parameters was carried out a month after harvesting and showed that mini-tubers in all variants had no signs of the late blight disease, rhizoctonia disease, common scab, etc.